PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM PSIKOLOGIS TERHADAP KESIAPAN UNTUK BERUBAH KARYAWAN PUSKESMAS KABUPATEN LOMBOK BARAT DALAM RANGKA AKREDITASI DAN KOMITMEN AFEKTIF SEBAGAI VARIABEL INTERVENING - mujiburrahman mujiburrahman (Master of Management, Mataram University, 2017)
This research is aimed at determining the significant effect of: (a) transformational leadership on readiness to change of employees of Health Centers in West Lombok. (b) transformational leadership on the affective commitment. (c) transformational leadership on the readiness to transform through affective commitment. (d) the psychological circumstances on preparedness to transform. (e) the psychological circumstances on affective commitment. (f) the psychological circumstances on preparedness to transform through the affective commitment of employees of Health Centers in West Lombok, (g) affective commitment of employees of health centers in West Lombok on preparedness to transform. This research is a causal associative with population of 508 employees of 7 health centers from which 84 employees are selected as samples through random sampling technique. The research showed that: (a) Transformational Leadership had no significant effect on readiness of employees of Health Centers in West Lombok to transform, (b) there is a significant effect of transformational leadership on affective commitment. (c) there is a significant effect transformational leadership on readiness to transform through affective commitment. (d) there is a significant effect of the psychological circumstances on readiness to transform. (e) there is a significant effect of the psychological circumstances on affective commitment. (f) there is a significant effect of the psychological circumstances on readiness to transform through affective commitment. (g) There is a significant effect of Affective Commitment to Readiness of employees of Health Centers in West Lombok to transform. Keywords: transformational leadership, psychological circumstance, commitment individual readiness to transform